Zrelost cevovodov neprekinjene dostave informacijskih rešitev - Četina, Luka; Pavlič, Luka (OTS 2026 Sodobne informacijske tehnologije in storitve: Zbornik 29. konference, 2026)
DevOps has established itself as an important approach to modern IT development, as it connects development and operational aspects and enables organizations to develop faster, more reliably. Since DevOps is not a single method, organizations introduce the practices gradually and differently, and it is difficult to assess how mature their processes are and which improvements are most urgent. Existing DevOps maturity models help in this, but they are usually focused on the organizational level, culture and processes, and the assessment is based on self-assessment with generally described criteria, which makes it difficult to compare assessments between teams. Less attention is paid to the specific technical implementation of automation - continuous delivery pipelines, through which a large part of DevOps practices are actually implemented. The paper presents a preliminary design of a model for assessing the maturity of CI/CD pipelines, based on criteria that can be verified directly in the pipeline configuration. The form covers six dimensions (build and integration automation, code testing and analysis, release and deployment automation, infrastructure as code, pipeline execution monitoring, and supply chain security), each with five criteria rated from 0 to 2 points. The total score (0–60 points) is mapped to five maturity levels, and the breakdown by dimension shows where the pipeline is mature and where it is lagging. The proposed model complements existing DevOps maturity models by enabling a systematic, repeatable, and potentially automated assessment of the technical maturity of an individual CI/CD pipeline.